(Invited) Intrinsic Unipolar SiOx-Based Resistive Switching Memory: Characterization, Mechanism and Applications. (8th September 2015) - Chang, Yao-Feng; Fowler, Burt; Zhou, Fei; Lee, Jack C.
Abstract : Intrinsic unipolar SiOx -based Resistive-RAM (ReRAM) characterization, mechanism and applications have been investigated. We investigate device structures, material compositions and electrical characteristics to realize ReRAM cells with high ON/OFF ratio, low static power consumption, low switching power, and high readout-margin using CMOS compatible SiOx -based materials. These ideas are combined with the use of horizontal and vertical device structure designs, composition optimization, electrical controlling and external factors for understanding resistive switching (RS) mechanism. Modeling of RS mechanism, including temperature effect, pulse response and carrier transport behaviors are performed, to develop a compact model in energy diagram, trap-level information in SiOx RS layer, even for computer-aided design (CAD) in very-large-scale integration (VLSI) design. Finally, synapse-based neuromorphic system is demonstrated in SiOx -based ReRAM, combining with bio-inspiration and biomimetics process illustrations. This work presents the comprehensively investigation of SiOx -based resistive switching characteristics, mechanisms, applications for future post-CMOS devices era.